Some Millennial Reflections on the State of Canadian Labour History - Morton, Desmond (Labour/Le Travailleur, 2000)
Abstract The suprise of being invited to comment on the state of Canadian labour history was exceeded by the honour. The explosive early growth of the field in the 1970s, and its domination by the team that created Labour/Le Travail, has concealed stasis and even a decline in the past decade, a harsh economic climate sent the paths of the labour movement and of younger historians in unexpected directions. Historians who believed they got closer to the present by understanding the past might reflect on misjudgments as well as successes.